2009
DOI: 10.1038/ismej.2009.45
|View full text |Cite
|
Sign up to set email alerts
|

The genome sequence of the psychrophilic archaeon, Methanococcoides burtonii: the role of genome evolution in cold adaptation

Abstract: burtonii has a high "IQ" (a measure of adaptive potential) compared to many methanogens.Numerous genes in these two over-represented COG categories appear to have been acquired from ε-and δ-proteobacteria, as do specific genes involved in central metabolism such as a novel B form of aconitase. Transposases also distinguish M. burtonii from other archaea, and their genomic characteristics indicate they play an important role in evolving the M. burtonii genome. Our study reveals a capacity for this model psychro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
164
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 148 publications
(171 citation statements)
references
References 106 publications
7
164
0
Order By: Relevance
“…Low rates of diazotrophy are also likely to occur in the mixolimnion (for example, by cyanobacteria) and monimolimnion (Figure 4b). In the monimolimnion, methanogens that encode nif genes, such as M. burtonii (Allen et al, 2009), could benefit from nitrogen fixation. Symbiotic relationships between diazotrophic archaea and SRB that have been reported to occur in marine environments (Dekas et al, 2009) may also occur in Ace Lake.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Low rates of diazotrophy are also likely to occur in the mixolimnion (for example, by cyanobacteria) and monimolimnion (Figure 4b). In the monimolimnion, methanogens that encode nif genes, such as M. burtonii (Allen et al, 2009), could benefit from nitrogen fixation. Symbiotic relationships between diazotrophic archaea and SRB that have been reported to occur in marine environments (Dekas et al, 2009) may also occur in Ace Lake.…”
Section: Resultsmentioning
confidence: 99%
“…Mineralization low abundance of Euryarchaeota (B2-5% of the total community), coupled to the very low potential for aerobic methane oxidation and the absence of 16S rRNA signatures for ANME Euryarchaeota. One of the two methanogenic archaea isolated from the lake, M. burtonii, possesses several genes most closely related to Epsilonproteobacteria and Deltaproteobacteria (Allen et al, 2009). The relative abundance of Epsilonproteobacteria and Deltaproteobacteria (Figure 2), and an overrepresentation of transposable elements (Figure 3 and Supplementary Figure S6) is consistent with gene exchange occurring within the microbial community in this zone, particularly between the Epsilonproteobacteria and Deltaproteobacteria and M. burtonii; the normalized number of transposases throughout the Ace Lake metagenome is two orders of magnitude higher than in marine metagenomes (for example, Global Ocean Survey).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Power-law distributions can imply a scale-free network, whereby the number of links to nodes provides a measure of node fitness (43), and the abundance of transposons has been linked to cold adaptation (44)(45)(46). The fact that tADL has the highest abundance and is highly connected to ISs (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This homeoviscosity is achieved by steric hindrances introduced into the lipid bilayer via incorporation of cis-unsaturated and branched-chain lipids, a decrease in average chain length, and an increase both in methyl branching and in the ratio of anteiso-to isobranching (Russell, 2007). More recently, several genomes from psychrophilic bacteria have been sequenced (Danchin, 2007;Casanueva et al, 2010) but only a few of them have been analyzed with respect to cold adaptation (Saunders et al, 2003;Rabus et al, 2004;Medigue et al, 2005;Methe et al, 2005;Riley et al, 2008;Allen et al, 2009;Ayala-del-Rio et al, 2010). However, the lack of common features shared by all these psychrophilic genomes has suggested that cold adaptation superimposes on pre-existing cellular organization and, accordingly, that the adaptive strategies may differ between the various microorganisms (Bowman, 2008;Piette et al, 2010).…”
Section: Introductionmentioning
confidence: 99%